Epidemiological and evolutionary dynamics on influenza B viruses in Kuala Lumpur, Malaysia between 2012 to 2014 / Oong Xiang Yong - Oong , Xiang Yong (2016)
Epidemiological and evolutionary dynamics of influenza B Victoria and Yamagata lineages remain poorly understood in the tropical Southeast Asia region, despite causing seasonal outbreaks worldwide. The aim of this study was to understand the epidemiological, evolutionary and transmission dynamics, as well as the clinical profiles of influenza B lineages circulating in Kuala Lumpur, Malaysia from 2012 to 2014 in a predominantly adult population. Furthermore, meteorological factors that may play a role in influenza seasonality in this country were also investigated. During the study period, nasopharyngeal swab samples collected from adult outpatients experiencing acute upper respiratory tract infection symptoms were screened for influenza viruses using a multiplex RT-PCR assay. Among 2,010/3,935 (51.1%) patients infected with at least one respiratory virus, 287 (14.3%) and 183 (9.1%) samples tested positive for influenza A and B viruses, respectively. Influenza-positive cases correlated significantly with meteorological factors - total amount of rainfall, relative humidity, number of rain days, ground temperature and particulate matter (PM10). Phylogenetic reconstruction of haemagglutinin (HA) gene from 168 influenza B viruses grouped them into Yamagata Clade 3 (65, 38.7%), Yamagata Clade 2 (48, 28.6%) and Victoria Clade 1 (55, 32.7%). With the phylogeny based on neuraminidase (NA) gene, 30 intra-clade (29 within Yamagata Clade 3, 1 within Victoria Clade 1) and 1 inter-clade (Yamagata Clade 2-HA/Yamagata Clade 3-NA) reassortants were identified. Study of virus temporal dynamics revealed a lineage shift from Victoria to Yamagata (2012-2013), and a clade shift from Yamagata Clade 2 to Clade 3 (2013 2014). Yamagata Clade 3 predominating in 2014 consisted of intra-clade reassortants that were closely related to a recent WHO vaccine candidate strain (B/Phuket/3073/2013), with the reassortment event occurred approximately 2 years ago based on Bayesian molecular clock estimation. Malaysian Victoria Clade 1 viruses v carried H274Y substitution in the active site of neuraminidase, which confers resistance to oseltamivir. Clinical and demographic data showed that Yamagata-infected patients were older and more likely to experience headache while Victoria-infected patients were more likely to experience nasal congestion and sore throat. This study describes the evolution of influenza B viruses in Kuala Lumpur, Malaysia and highlights the importance of continuous surveillance to inform influenza vaccination policies in this region.